Service Strategy Of RSUD Brigjend H. Hasan Basry Kandangan To Health Insurance Customers After The Pandemic - Faqih El Wafa; Mariam Mariam; Faridah Faridah (IAIN Palopo, 2023)
This researcher departed from the increasing number of health insurance customers in treatment at RSUD Brigjend H. Hasan Basry Kandangan. Therefore, RSUD Brigjend H. Hasan Basry Kandangan acts as a good service provider to provide trust to customers. This study aimed to determine the health customer service strategy used by RSUD Brigjend H. Hasan Basry Kandangan in delivering services per service standards and Islamic principles. This research is field research with a qualitative approach. Therefore, to collect data, interview techniques are used directly with informants. After conducting research, the author describes, describes, and analyzes the data obtained from informants regarding service strategies and the application of Islamic service principles. The result of this research is that the service strategy used by Brigjend H. Hasan Basry Kandangan Hospital follows the service standards of regional public hospitals by using the dimensions of the promised service. The service from the Islamic perspective has been applied following the principles of Islamic service and the Fatwa of the National Sharia Council - Indonesian Ulema Council (DSN-MUI) Number 107/DSN-MUI/X/2016